Simulation on using cross-correlation technique for two-phase liquid/gas flow measurement for Ultrasonic Transmission Tomography - Nor Muzakkir, Nor Ayob; Sazali, Yaacob, Prof. Dr.; Zulkarnay, Zakaria; Mohd Hafiz, Fazalul Rahiman; Ruzairi, Abd Rahim (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher’s homepage at http://ieeexplore.ieee.org/